Analisis Customer Relationship Management System (CRP) Pada Kepuasaan Pelanggan: Studi Di Bank BTPN Syariah Cabang Jepon Kabupaten Blora - Tri Lestari Hadiati; Umi Nur Faizatulmuna (Public Service and Governance Journal, 2024)
One of the customers at BTPN Syariah Bank Jepon Branch Blora Regency reported his complaint to the Community Officer (CO) there is one officer who is less friendly serving customers, another officer the service is long so that customers have not been satisfied. This is complained by customers related to the quality of service and employee competence provided greatly affects customer satisfaction. In this descriptive qualitative research intends to explain this social phenomenon in detail. Researchers attempt to develop concepts while collecting facts in the field. Secondary Informants are BTPN Syariah customers and Key Informants are some employees and supervisors in BTPN Syariah Jepon Branch, Blora Regency. The 30 customers were obtained from questionnaires that were processed using cumulative score and percentage (%). Looking at Fornell's Theory and Kotler's Theory and some data analysis, it can be concluded that customer relationship management (CRP) on customer satisfaction at BTPN Syariah Bank Jepon Branch, Blora Regency can be said to be quite good. It is proven that customer satisfaction by calculating the cumulative score is calculated as 72%. In addition, most of the secondary informants, namely as much as 50%, said that Bank employees have done their job in accordance with existing SOPs, employees have good quality in serving, employees also have the ability to attract other customers, explanations from employees to customers are also easy to understand and understand, therefore customers believe in bank products. This shows that with the help of employees and existing customers, they can recommend potential new customers. Therefore, BTPN Syariah employees need to maintain better customer relationship management (CRM).